The Burwood Academy: incorporating the principles of the independent living paradigm into rehabilitation research. Issue 3 (19th July 2019) - Bourke, John; Nunnerley, Joanne; Snell, Deborah; Sinnott Jerram, Anne
Abstract : Purpose: The independent living (IL) movement is a social movement but also an analytic paradigm which can be used to inform and shape rehabilitation research and practice. The purpose of this paper is to describe how the principles of DeJong's IL paradigm have been used to develop a guiding framework for the Burwood Academy, a rehabilitation and disability research organisation in New Zealand. The Burwood Academy drew on the consumer empowerment principles inherent in DeJong's IL paradigm, whereby the person learns to take control of the rehabilitation process, on which to promote consumer empowerment in all of the Academy's endeavours. Design/methodology/approach: This paper reports on three investigative phases of work: a stakeholder dialogue, a narrative review and a benchmarking exercise that collectively enabled the development of a working framework based on DeJong's IL paradigm. Findings: This paper highlights pragmatic strategies that are used to better promote consumer inclusion in the research process, build researcher capacity among consumers and clinicians, and promote knowledge translation through a range of tertiary and clinical education forums. Research limitations/implications: The results of this study identified numerous ways to promote consumer empowerment in research. Future research is needed to explore the effectiveness of the proposed framework further. Practical implications: This paper suggests potential avenues to address the complexities of promoting the role of the "expert consumer" imbedded in clinical environments where this is not usually a priority in training and practice of health professionals. Originality/value: This paper fulfils an identified need to study more pragmatic ways to promote consumer empowerment in both clinical and research settings.